The genus Manota Williston (Diptera: Mycetophilidae) in the Congo basin with description of five new species - Kurina, Olavi; Hippa, Heikki (Zootaxa, 2014)
The Manota species in the Congo basin are reviewed and 17 species are recorded. The following five new species are described: M. grootaerti sp. n., M. peltata sp. n., M. peltigera sp. n., M. reclinata sp. n., and M wittei sp. n. New records of the following species are presented: M. freerki Hippa & Kurina, 2012, M. issongo Matile, 1972, M. kibaleensis Hippa & Kurina, 2012, M. lachaisei Matile, 1972, M. mabokeensis Matile, 1972, M. mazumbaiensis Søli, 1993, M. petiolata Hippa & Kurina, 2012, M. pilosa Hippa & Kurina, 2012, M. relicina Hippa & Kurina, 2012, M. senticosa Hippa & Kurina, 2012 and M. teocchii Matile, 1972. Manota issongo is redescribed, including detailed illustration of the male hypopygium. The number of Afrotropical Manota species is increased to 56.